Low temperature simple aqueous phase chemical synthesis and characterization of ZnO thin films. (2017) - Shinde, D.B.; Ghanwat, V.B.; Khot, K.V.; Kondalkar, V.V.; Mane, R.M.; Bagade, C.S.; Jagdale, S.K.; Mane, R.K.; Bhosale, P.N.
Abstract: Zinc oxide (ZnO) nanorods were successfully deposited on the glass and fluorine doped tin oxide coated glass substrate in an aqueous alkaline medium using zinc acetate, ethylene diamine, hexamethylene tetraamine and ethanol by simple chemical reflux method at low temperature. An Optical, structural, morphological compositional and photoelectrochemical (PEC) properties of ZnO thin films were investigated. Optical absorption study of the sample shows band gap value 3.24 eV. The X-ray diffraction (XRD) pattern indicates that the deposited material is nanocrystalline and nanorods formation takes place along (002) plane having hexagonal wurtzite crystal structure. The scanning electron microscopy (SEM) images demonstrate existence of hexagonal nanorods with average50nm lengths and 10 nm diamete.The X-ray photoelectron spectroscopy (XPS) study confirms well composed thin film formation. The PEC study revel that material exhibit photo conversion efficiency 1.84% for solar cell application.